Project business management - Lehmann, Oliver F.; Taylor and Francis (Boca Raton, FL : Auerbach Publications, an imprint of Taylor and Francis, 2018)
Roughly half of all project managers have to lead customer projects as profit centers on contractor side with two big objectives: making the customer happy and bringing money home. Customer projects are a high-risk business on both sides, customers and contractors, but the dynamics of this business have so far been mostly ignored in literature. The book is intended to fill this gap. The book helps project managers better understand the dynamics of customer projects under contract from business development through handover and find solutions for common problems. A central aspect is international contract laws, an often underestimated factor in projects.
chapter 1 Laying Out the Scenery: The Business Side of Project Management -- chapter 2 The Diffi cult Way to the Contract -- chapter 3 Contracting -- chapter 4 Managing Complex and Dynamic PSNs -- chapter 5 Project Business Management and Crisis Management.
Keywords: Engineering -- Management; Information technology -- Management; COMPUTERS / Information Technology; TECHNOLOGY & ENGINEERING / Engineering (General)